A New Method for Evaluating the Conformations and Normal Modes of Macromolecule Vibrations with a Reduced Force Field. 2. Application to Nonplanar Distorted Metal Porphyrins - Unger, Esko; Beck, Michael; Lipski, Robert J; Dreybrodt, Wolfgang; Medforth, Craig J; Smith, Kevin M; Schweitzer-Stenner, Reinhard (The journal of physical chemistry. B, 1999)
We have developed a novel method for molecular mechanics calculations and normal-mode analysis. It is based on symmetry of local units that constitutes the given molecule. Compared with general valence force field calculations, the number of free parameters is reduced by 40−80% in our procedure. It was found to reproduce very well the vibrational frequencies and mode compositions of aromatic compounds and porphyrins, as shown by comparison with DFT calculations. A slightly altered force field obtained from Ni(II) porphin was then used to calculate the structure and the normal modes of several meso-substituted Ni(II) porphyrins which are known to be subject to significant ruffling and/or saddling distortions. This method satisfactorily reproduces their nonplanar structure and Raman band frequencies in the natural abundance and isotopic derivative spectra. The polarization properties of bands from out-of-plane modes are in accordance with the predicted nonplanar distortions. Moreover, we found that some of the modes below 800 cm-1 which appear intense in the Raman spectra contain considerable contributions from both in-plane and out-of-plane vibrations, so that the conventional mode assignments become questionable. We also demonstrate that the intensity and polarization of some low-frequency Raman bands can be used as a (quantitative) marker to elucidate type and magnitude of out-of-plane distortions. These were recently shown to affect heme groups of hemoglobin, myoglobin, and, in particular, of cytochrome c.